2016
DOI: 10.1074/jbc.c115.700492
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) Screen Identifies NEK7 as an Essential Component of NLRP3 Inflammasome Activation

Abstract: Inflammasomes are high molecular weight protein complexes that assemble in the cytosol upon pathogen encounter. This results in caspase-1-dependent pro-inflammatory cytokine maturation, as well as a special type of cell death, known as pyroptosis. The Nlrp3 inflammasome plays a pivotal role in pathogen defense, but at the same time, its activity has also been implicated in many common sterile inflammatory conditions. To this effect, several studies have identified Nlrp3 inflammasome engagement in a number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
276
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(286 citation statements)
references
References 27 publications
7
276
1
2
Order By: Relevance
“…YopJ appears to be a major driver of cell death, with some inhibitory effects mediated by YopM. Very recent findings on cell death mediated by caspase-11 and caspase-1 via gasdermin D (43,44) and by NEK7 via NLRP3/caspase-1 (45,46) suggest that there are a number of additional players involved in regulation of inflammasome and pyroptosis pathways. Furthermore, other bacterial components, such as YopK (47), could differently impact the various death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…YopJ appears to be a major driver of cell death, with some inhibitory effects mediated by YopM. Very recent findings on cell death mediated by caspase-11 and caspase-1 via gasdermin D (43,44) and by NEK7 via NLRP3/caspase-1 (45,46) suggest that there are a number of additional players involved in regulation of inflammasome and pyroptosis pathways. Furthermore, other bacterial components, such as YopK (47), could differently impact the various death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is unclear how AIM2 activation is prevented during mitosis. One possibility is that AIM2 is regulated by mitotic factors as reported for NLRP3 (69,70). We previously showed that treatment with HIV-PIs triggers a transcriptional and translational reprogramming via the integrated stress response.…”
Section: Discussionmentioning
confidence: 99%
“…CARD, caspase recruitment domain; CC, coiled-coil; PYD, pyrin domain. New insights into the mechanism of NLRP3 activation might be provided by three recent reports that have identified an unexpected role for NIMA-related kinase 7 (NEK7) in this process [14][15][16] . These studies found that NEK7 is essential for NLRP3 activation in response to both canonical and non-canonical stimuli and that it acts downstream of potassium efflux.…”
mentioning
confidence: 98%
“…b | Potassium efflux is a common event that is associated with a diverse array of NLRP3 stimuli 13 . NLRP3 activation also requires NIMA-related kinase 7 (NEK7), which binds to the NLRP3 leucine-rich repeats (LRRs) and is required for its oligomerization [14][15][16] . c | NLR family, apoptosis inhibitory proteins (NAIPs) function as direct receptors for bacterial flagellin and the type 3 secretion system (T3SS) needle and rod subunits 21,22 .…”
mentioning
confidence: 99%